2008
DOI: 10.1177/0021998308093913
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Long-term Creep and Fatigue Strengths of Polymer Composites Based on Accelerated Testing Methodology

Abstract: The applicability of our developed accelerated testing methodology (ATM) based on the time—temperature superposition principle (TTSP) and others for the prediction of long-term fatigue life of polymer matrix composites is performed experimentally and theoretically. A formulation method of master curves of creep and fatigue strengths for polymer matrix composites is introduced based on ATM. The master curves of creep and fatigue strengths for the typical three directions of unidirectional CFRP, that is the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 25 publications
1
68
0
Order By: Relevance
“…The details for test methods and tests results shown here were published in our previous paper. 6 Therefore, the explanation presented here addresses the formulations of ATM-2 using the measured data.…”
Section: Specimens and Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details for test methods and tests results shown here were published in our previous paper. 6 Therefore, the explanation presented here addresses the formulations of ATM-2 using the measured data.…”
Section: Specimens and Test Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Furthermore, we have proposed a method of formulating master curves based on the simple equation as functions of time to failure, temperature, loading frequency, and number of cycles to failure. 6 However, this equation has not directly taken into account the viscoelastic coefficients of matrix resin. Therefore, the equation cannot be applied to the life Materials System Research Laboratory, Kanazawa Institute of Technology, Japan prediction of CFRP laminates exposed to an actual load and temperature history.…”
Section: Introductionmentioning
confidence: 99%
“…A master curve of these measured storage moduli can be formed by shifting the data in the time axis. Miyano from Kanazawa Institute of Technology in Japan has pioneered this approach for many years [13] . Figure 12 shows the storage modulus master curve of Hexcel 8552 matrix system, baseline for MMF.…”
Section: Master Curves From Accelerated Testing Methods (Atm)mentioning
confidence: 99%
“…It is worth noting that fatigue models by Miyano et al [9,10,11] and Reifsnider et al [12] are meant to account for viscoelastic effects while the model by Epaarachchi and Clausen [13] includes the effect of frequency under the assumption of negligible hysteretic heating. However, Guedes [24] has suggested that the linear cumulative law employed by Myiano may not fare well for complex fatigue loads or long lifetimes.…”
Section: Introductionmentioning
confidence: 99%